Vegetative Growth of Paprika Plant (Capsicum annum var grossum) at Three Diferent Sound Frequencies - Ega Meydiyawati; Riza Linda; Sitti Ifadatin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Paprika (Capsicum annum var grossum) is a horticultural commodity with high economic value. Cultivation of paprika is currently still relatively low, for West Kalimantan. This research was conducted to see the effect of exposure to different sound frequencies on the growth of Paprika (Capsicum annum var. grossum) plants. The time for the study was from May 16 2022 to August 14 2022. This study used a Completely Randomized Design (CRD) which had 4 different treatments namely control, 396 hz sound exposure, 528 hz sound exposure, and 660 hz sound exposure. Data were analyzed using one way ANOVA followed by Duncan's test with a certainty level of 0.05%. The results showed that exposure to 528 sound gave the best results on plant height, leaf area, pore length, pore width, chlorophyll B, and total chlorophyll. In conclusion, that exposure to sound can increase the growth of pepper plants.